Mechanisms Underlying Metformin-Induced Secretion of Glucagon-Like Peptide-1 from the Intestinal L Cell - Mulherin, Andrew J.; Oh, Amy H.; Kim, Helena; Grieco, Anthony; Lauffer, Lina M.; Brubaker, Patricia L. (Endocrinology (Philadelphia), 2011)
Glucagon-like peptide-17-36NH2 (GLP-1) is secreted by the intestinal L cell in response to both nutrient and neural stimulation, resulting in enhanced glucose-dependent insulin secretion. GLP-1 is therefore an attractive therapeutic for the treatment of type 2 diabetes. The antidiabetic drug, metformin, is known to increase circulating GLP-1 levels, although its mechanism of action is unknown. Direct effects of metformin (5–2000 μm) or another AMP kinase activator, aminoimidazole carboxamide ribonucleotide (100–1000 μm) on GLP-1 secretion were assessed in murine human NCI-H716, and rat FRIC L cells. Neither agent stimulated GLP-1 secretion in any model, despite increasing AMP kinase phosphorylation (P < 0.05–0.01). Treatment of rats with metformin (300 mg/kg, per os) or aminoimidazole carboxamide ribonucleotide (250 mg/kg, sc) increased plasma total GLP-1 over 2 h, reaching 37 ± 9 and 29 ± 9 pg/ml (P < 0.001), respectively, compared with basal (7 ± 1 pg/ml). Plasma activity of the GLP-1-degrading enzyme, dipeptidylpeptidase-IV, was not affected by metformin treatment. Pretreatment with the nonspecific muscarinic antagonist, atropine (1 mg/kg, iv), decreased metformin-induced GLP-1 secretion by 55 ± 11% (P < 0.05). Pretreatment with the muscarinic (M) 3 receptor antagonist, 1-1-dimethyl-4-diphenylacetoxypiperidinium iodide (500 μg/kg, iv), also decreased the GLP-1 area under curve, by 48 ± 8% (P < 0.05), whereas the antagonists pirenzepine (M1) and gallamine (M2) had no effect. Furthermore, chronic bilateral subdiaphragmatic vagotomy decreased basal secretion compared with sham-operated animals (7 ± 1 vs. 13 ± 1 pg/ml, P < 0.001) but did not alter the GLP-1 response to metformin. In contrast, pretreatment with the gastrin-releasing peptide antagonist, RC-3095 (100 μg/kg, sc), reduced the GLP-1 response to metformin, by 55 ± 6% (P < 0.01) at 30 min. These studies elucidate the mechanism underlying metformin-induced GLP-1 secretion and highlight the benefits of using metformin with dipeptidylpeptidase-IV inhibitors in patients with type 2 diabetes.